An intrinsically stretchable and compressible Zn–air battery. Issue 35 (30th March 2020) - Wang, Yueyang; Liu, Jie; Feng, Yuping; Nie, Ningyuan; Hu, Mengmeng; Wang, Jiaqi; Pan, Guangxing; Zhang, Jiaheng; Huang, Yan
Abstract : An intrinsically 300% stretchable and 85% compressible Zn–air rechargeable battery with good electrochemical performances was fabricated for the first time. Abstract : An intrinsically highly stretchable and compressible Zn–air rechargeable battery with good electrochemical performance was fabricated for the first time. It exhibits the merits of 300% intrinsic stretchability and 85% intrinsic compressibility with excellently retained electrochemical performance, a decrease in catalyst cost of 40 times, the fewest number of components and facile fabrication.